Pengaruh Gaya Hidup dan Promosi Terhadap Keputusan Pembelian Sepeda Listrik di Duta Elektronik Kota Bima - Dwi Alladin; Irma Mardian (Institute of Advanced Knowledge and Science, 2023)
Lifestyle is closely related to developments over time. Your own lifestyle is more likely to follow current trends. Along with the development of the era of globalization, it has a strong influence on all dimensions of people's lives. Lifestyle is a person's way of having values ​​within themselves. They will make the right consumption choices based on their lifestyle behavior. The aim of this research is to determine the influence of lifestyle and promotion on the decision to purchase an electric bicycle at Duta Elektronik Bima. The population in this study were all consumers who had purchased an electric bicycle at Duta Elektronik. The sampling technique in this study used a purposive sampling technique, namely using the criteria of people who had bought electric bicycles at Duta Elektronik stores and had been exposed to Duta Elektronik promotions. The tests used are validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression test, t test, F test and determination test. This research concludes that lifestyle and promotion partially have a positive and significant effect on purchasing decisions.